2017
DOI: 10.4236/abb.2017.88018
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnostic Test Kits Detection of Malaria Parasites among Pregnant Women Attending Antenatal in Selected Hospitals in Anyigba, Kogi State, Nigeria

Abstract: A study was carried out to determine the status of malaria in four (4) selected hospitals in Anyigba, Dekina Local Government Area, Kogi State. A total of 300 pregnant women attending antenatal were tested for malaria parasite using rapid diagnostic test kits. Blood samples were obtained from finger by pricking and tested for malaria parasites. Structured questionnaires were administered to the pregnant women to obtain relevant information on the clinical and social aspects of malaria. A prevalence of 13.0% (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
0
1
Order By: Relevance
“…For instances, prevalence of 2.0% and 7.7% reported in Lagos [18,26], 11% in Sokoto [19], 7.3% in Port Harcourt, [3], 2.3% in Chittagny, Bangladesh [27] and 4.7% in Colombia [16]. In contrast, the prevalence recorded in the present study is significantly lower than 13% reported in Dekina, Northcentral Nigeria [28], 36.8% in Southwest Nigeria [4] and 41% in Southeastern Nigeria [29]. These studies employed light microscopy and RDT kits with similar sensitivity, thus, the disparity could be attributed to factors such as malaria transmission intensity and control measures among other factors.…”
Section: Discussioncontrasting
confidence: 70%
“…For instances, prevalence of 2.0% and 7.7% reported in Lagos [18,26], 11% in Sokoto [19], 7.3% in Port Harcourt, [3], 2.3% in Chittagny, Bangladesh [27] and 4.7% in Colombia [16]. In contrast, the prevalence recorded in the present study is significantly lower than 13% reported in Dekina, Northcentral Nigeria [28], 36.8% in Southwest Nigeria [4] and 41% in Southeastern Nigeria [29]. These studies employed light microscopy and RDT kits with similar sensitivity, thus, the disparity could be attributed to factors such as malaria transmission intensity and control measures among other factors.…”
Section: Discussioncontrasting
confidence: 70%